Role of laboratory values in determining disease activity in juvenile rheumatoid arthritis - Arwin A. P. Akib; Alan R. Tumbelaka; Titi S. Sularyo; Dina S. Daliyanti (Indonesian Pediatric Society, 1999)
Juvenile rheumatoid arthritis (JRA) is an autoimmune joint disease characterized by supression of disease activity. To confirm clinical criteria in determining disease activity, several laboratory parameters, such as haemoglobm level, leucocyte count, thrombocyte count, erythrocyte sedimentation rate (ESR), C reactive protein (CRP), serum concentration of immunoglobulin and complement are considered important. This retrospective study was undertaken to find out whether the same correlation was also existed our patients trend. Bivariate analysis was used to study 113 episodes of disease activity in 46 patients with JRA from October 1983-0ctober 1997. Each episode of disease activity was clinically classified as either active or inactive according to American Rheumatism Assocation (ARA). It was found that CRP and disease activity correlated significantly (p=O.04). The disease activity was not associated with anemia, leukocytosis, thrombocytosis, increased level of ESR, high serum immunoglobulin concentration, or increased level of complement. Heterogenous origin in 3 types of IRA and limited study subjects may affect these results. In conclusion, besides clinical judgment of disease activity, CRP can be added and used as an objective measure of disease activity.